Philosophy in the twentieth century - Ayer, A. J. (Counterpoint, 1984)
This contribution to the philosophy was originally conceived as a sequel to Bertrand Russell's A history of Western philosophy. It fulfils this intention to the exten that it also confines itself to the West, that , apart from a revaluation of William James and a considerably expanded treatment of Russell himself, it takes up the story at the point where he left off, and that rather than mention a whole host of philosophers who have made some contribution to the subject, and devote a few lines to each,...